Investigation of wear resistance of polymer-coated radial bearing running on micropolar lubricant - V. I. Kirishchieva; M. A. Mukutadze (Омский научный вестник)
The article is devoted to one of the important problems of increasing the wear resistance of tribosystems by applying an antifriction polymer composite coating containing a groove that operates in a hydrodynamic mode to the tribocontact surface. Based on the equation of the flow of truly viscous liquid for a «thin layer» and the continuity equation, a self-similar solution is found taking into account the groove and without taking into account the groove, as a result, the velocity and pressure fields in the groove and on the surface of the polymer antifriction composite coating are determined, as well as the load capacity and friction force allowing to determine the increase in wear resistance; an increase in duration of the hydrodynamic regime. The results of numerical analysis of the obtained theoretical calculation models and experimental evaluation of the proposed design are also presented in order to verify and confirm the effectiveness of the obtained theoretical models.